Organizational behavior - McShane, Steven L. (McGraw-Hill, 2007)
Organizational Behavior (essentials) offers the same quality of contemporary knowledge, global coverage, and classroom support that has made the comprehensive hardbook text, Organizational Behavior, by Steve McShane and Mary Ann Von Glinow, one of the fast growing OB texts on the market.